MANAJEMEN ORGANISASI PONDOK PESANTREN - Fauzi, Faruq Tri (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2013)
Boarding organization was important in order to deliver the organizations progress. Role of Pesantren help in learning framework motivation organizational behavior related to creativity. Thus management education is the dominant factor in the framework of a nations progress. Stigma would adversely boarding school management Pesantren in the state seems to have not gone right. Entering the era of globalization today, the existence of Pesantren as the oldest Islamic institution in the state would be managed manaj with more professional if do not want to be left as the stakeholder community. Todays global current information and knowledge to make the world more accessible community. For it not to look for the possibility that once made Pesantren Islamic study center and a practitioner at once, that in time became interested in it and left the service user community. To the mutual duty of the governor / nanny Pesantren do and make efforts and improve strategies so that Pesantren as Islamic educational institutions have their own special features in time reference of Muslims in the world. They will then be turned toward Pesantren and make Pesantren as the primary alternative community education.